2016
DOI: 10.1136/ejhpharm-2016-000944
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antiretroviral therapy modification in routine clinical practice in the management of HIV infection

Abstract: ObjectivesThe main goal was to assess the reasons for antiretroviral therapy (ART) change in patients with HIV in a hospital setting in routine clinical practice. The economic impact of ART modification was also analysed.MethodsPatients with HIV who changed their ART between 24 November and 24 December 2014 were registered. Length of initial therapy, type of ART before and after therapy modification, and reasons for the ART change were analysed. To assess the economic impact, antiretroviral drug costs at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…Ten studies were summarized in the previous review [ 11 ]. Three additional studies were identified and are reported in this publication [ 23 , 44 , 45 ]. One study, evaluating overall ART changes in 3850 PLWH, found that modifying therapy resulted in a mean additional cost of €14 (SD €216; range −€528 to +€831) per month per patient [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies were summarized in the previous review [ 11 ]. Three additional studies were identified and are reported in this publication [ 23 , 44 , 45 ]. One study, evaluating overall ART changes in 3850 PLWH, found that modifying therapy resulted in a mean additional cost of €14 (SD €216; range −€528 to +€831) per month per patient [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three additional studies were identified and are reported in this publication [ 23 , 44 , 45 ]. One study, evaluating overall ART changes in 3850 PLWH, found that modifying therapy resulted in a mean additional cost of €14 (SD €216; range −€528 to +€831) per month per patient [ 44 ]. Toxicity and therapy simplifications were cited as the leading causes for regimen changes [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En este estudio retrospectivo describimos la evolución de la terapia antirretroviral en los últimos 5 años. Si analizamos estudios previos, como el de Korten et al [ 6 ] donde analizaban los motivos de cambio de TAR de 1ª línea (2011-2017), la interrupción por intolerancia/toxicidad fue la principal causa, mismo resultado que el obtenido en el estudio de SobrinoJiménez C. [ 7 ] durante diciembre del 2014. En ambos estudios el esquema ITIAN más frecuente era el que contenía tenofovir disoproxil en su forma de sal de fumarato (TDF), destacado por su toxicidad renal y ósea, y, a pesar de que estas toxicidades ya venían descritas en las guías, no fue hasta el 2018 cuando la guía geSIDA [ 8 ] menciona en sus recomendaciones de esquemas preferentes el uso únicamente de la forma tenofovir alafenamida (TAF).…”
Section: Discussionunclassified
“…The management of HIV predominantly revolves around a multifaceted approach, encompassing highly active antiretroviral therapy (HAART), consistent monitoring of viral load and CD4 cell count, and the implementation of lifestyle modifications conducive to overall health. [1][2][3][4] HAART stands as the established standard for managing HIV infection, a condition that currently remains without a definitive cure. [5][6][7] The concurrent administration of a combination of antiretroviral drugs, each targeting distinct viral components, serves to uphold the immune system's functionality and act as a deterrent against potentially fatal opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%